PENYELESAIAN SENGKETA INFORMAL BERBASIS KOMUNITAS ADAT TERPENCIL DI KEPULAUAN KANGEAN (Pilihan Hukum dan Posisi dalam Sistem Hukum Negara) - Rina Yulianti; Sri MaharaniMTV (Jurnal Dinamika Hukum, 2012)
The principle of legal procedure which is simple, fast and low cost cannot conducted in term of practice of the court in an Indigenous society. Although, it is implemented in such of remote island, the informal dispute resolution based on indigenous community in Kangean Island is expected to simplify an society access to justice and equality before the law. This research aims at giving the legitimacy of the informal dispute settlement mechanism to the indigenous society, which is far away from the access of the formal justice. The methods used in this research are a combination of statute, conceptual and case approach. The result of this research of this research states that chances of building a justice, at the village level can be embodied through such of judicial construction of judiciary function into a village government system. Through the codification of customary laws and traditional mechanisms in to the structures of village governance is expected to provide legal protection for the informal dispute resolution                                                        Key words : Informal dispute resolution, access to justice, formal justice